Formation of TEM- and XRD-undetectable gold clusters accompanying big gold particles on TiO2eSiO2 supports; Solid State Sciences; Vol. 10, iss. 7 - Bogdanchikova N.; Pestryakov A. N. Aleksey Nikolaevich; Farias M. H.; Diaz J. A.; Avalos M.; Navarrete J. (2008, 2008)
Sol–gel method allows obtaining complex Ti–Si oxide supports possessing the effect of strong metal–support interaction and favouring the stabilisation of gold in the form of small charged gold clusters. TEM and XRD measurements show the samples containing big gold particles with average size more than 90 nm. However, Rietveld XRD refinement revealed a very low (≤5%) relative amount of large particles on mixed oxide supports. Highly dispersed gold species undetectable by XRD and TEM on TiSi supports provide the main contribution to total amount of gold due to extremely high surface area of these mixed oxides. The combination of DRS, Rietveld XRD analysis and XPS methods was effective for registration and characterisation of these dispersed gold species. The formation of such gold species should be taken into account when studying the nature of gold active sites, as they can be the participants of the catalytic process instead of TEM-detectable metal particles or along with them.